Webquest Methodology in University and School Education: A Systematic Review - Villegas-Dianta, Cristian Adrián (2025)
Introduction. The Webquest is a commonly used educational methodology in schools and universities that poses problem-based situations for students to solve, utilizing technology and promoting collaboration. The COVID-19 pandemic has highlighted the benefits of the Webquest approach, though it is not without its own set of challenges. Objective. The purpose of this study is to review recent literature on the Webquest methodology and to evaluate its advantages and disadvantages in the realm of education and learning. Methods. A systematic review of the literature was conducted using a selection of databases, including Redalyc, Dialnet Plus, Scielo, WoS, ProQuest, EBSCO, and ERIC, with a search limited to Spanish-language articles published between 2017 and 2022. Keywords were used as the basis of the search, and the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) flowchart was utilized as a search strategy. 662 articles were initially identified, of which 10 met the inclusion criteria for the study. Conclusions. The review of the literature suggests that the Webquest methodology is useful in facilitating student learning but that there are some limitations, such as the time required to develop the Webquest, and the technological proficiency required of the educators in order to construct it.